Activity Levels of 210Po, 210Pb and Other Radionuclides (134Cs, 137Cs, 90Sr, 110mAg, 238U, 226Ra and 40K) in Marine Organisms From Coastal Waters Adjacent to Fuqing and Ningde Nuclear Power Plants (China) and Radiation Dose Assessment - Sun, Jiang; Men, Wu; Wang, Fenfen; Wu, Junwen (Frontiers in Marine Science, 2021)
With the rapid development of nuclear power, the radiation impacts on edible marine organisms and the potential radiation risks to humans have become of considerable concern to public health. In this study, the activities of 210Po and 210Pb as well as those of other radionuclides in fishes (Mugil cephalus, Konosirus punctatus, Largehead hairtail, Larimichthys polyactis), crustaceans (Mantis shrimp, Parapenaeopsis hardwickii, Portunus trituberculatus), bivalves (Crassostrea gigas, Sinonovacula conzcta) and macroalgae (Gracilaria, Porphyra) collected in the coastal area adjacent to the Fuqing and Ningde nuclear power plants (NPPs) were determined. The activity range of 210Po and 210Pb was 0.60-48.09 and 0.07-2.76 Bq/kg fresh weight respectively, with 210Po/210Pb activity ratios of 1.1-189.7. The ranking of 210Po activity levels in marine organisms was bivalve molluscs > crustaceans > fishes > macroalgae. The calculated bioconcentration factors of 210Po and 210Pb were 636-44944 and 3-1226 L/kg, respectively. These values provide a new supplement to the IAEA reference database. The radiation dose rates for these marine organisms ranged from 0.037 to 1.531 μSv/h, which was much lower than the ERICA ecosystem screening benchmark of 10 μGy/h. The calculated committed effective dose received by humans from ingestion of these marine organisms was 0.06-2.99 mSv. Overall, 210Po was the dominant radiation dose contributor in marine organisms and humans, whereas the dose contributions from the artificial nuclides 90Sr and 137Cs was negligible and can be ignored.